Clinical, parasitological, and serological characteristics of toxoplasmosis in felines (Felis catus) infected with isolates i and III of Toxoplasma gondii - Pires Teixeira, Weslen Fabricio; Vieira, Dielson da Silva [UNESP]; Zanetti Lopes, Welber Daniel; Felippelli, Gustavo; Bueno Franco, Regina Maura; Branco, Nilson; Soares, Vando Edesio; Saraiva Bresciani, Katia Denise [UNESP]; Costa, Alvimar Jose da [UNESP] (Univ Estadual Londrina, 2019)
Toxoplasmosis is a parasitic disease caused by the protozoan Toxoplasma gondii, characterized by a clinical or subclinical infection attributed mainly to the isolate of the parasite responsible for the infection. Although domestic felines are considered the only urban hosts of this parasite and, consequently, the animals responsible for perpetuating T gondil cycle in this environment, there is still a lack of information regarding the potential of different strains/isolates of this parasite and appearance of clinical signs during infection in domestic felines. In this context, the objective of the present study was to evaluate the clinical, parasitological, and serological characteristics of toxoplasmosis in felines infected with T. gondli isolates type I (RH strain) and III (P strain). Twelve healthy and serologically negative felines were selected for T gondii (IgG titer < 16). These animals were divided into three experimental groups, GI: (P1, P2, P3, and P4) inoculated with 600 cysts of T gondii (P strain), GII: (RH1, RH2, RH3, and RH4) inoculated with 2 x 10(5) tachyzoites (RH strain), and GIII: (C1, C2, C3. and C4) uninoculated. From the seventh day before (day 7) to the 70th day after inoculation (DAD, the animals were observed daily to verify the occurrence of alterations in the digestive, nervous, locomotor, cardiorespiratory, and urinary systems, as well as skin and appendages. The clinical signs most observed in felines inoculated with T gondii were apathy, hyporexia, slivering, nasal secretion, ocular secretion, and diarrhea. The results obtained in this study allow inferring that T gondii isolate type I (RH strain) was more pathogenic to feline species than isolate type III (P strain), although both showed clinical symptomatology in all infected animals.
Keywords: Toxoplasmosis; Parasites; Experimental infection; Oocysts